2010
DOI: 10.1007/s11259-010-9349-6
|View full text |Cite
|
Sign up to set email alerts
|

The identification of intestinal M cells in the sacculus rotundus and appendix of the Angora rabbit

Abstract: The present study was aimed at the immunohistochemical demonstration of M cells, found in the follicle-associated epithelium (FAE) of the sacculus rotundus (SR) and appendix of the Angora rabbit, using anti-vimentin primary antibodies, and at the determination of certain fine structural characteristics. Ten adult Angora rabbits constituted the material of the study. Immunohistochemical staining revealed that many cells composing the FAE, which covered the dome regions of the SR and appendix, reacted positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…In addition, the sacculus rotundus, an enlarged muscular ampulla at the distal end of the ileum, is a unique gut-associated lymphoid tissue in rabbits that plays an important role in intestinal innate immunity and adaptive immunity (Beyaz et al, 2010). In the present study, our results revealed that only the stalkless dectin-1B isoform is expressed in rabbit sacculus rotundus, and has low proinflammatory cytokines expression in nonrisk genotype even in severe intestinal inflammation stages.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, the sacculus rotundus, an enlarged muscular ampulla at the distal end of the ileum, is a unique gut-associated lymphoid tissue in rabbits that plays an important role in intestinal innate immunity and adaptive immunity (Beyaz et al, 2010). In the present study, our results revealed that only the stalkless dectin-1B isoform is expressed in rabbit sacculus rotundus, and has low proinflammatory cytokines expression in nonrisk genotype even in severe intestinal inflammation stages.…”
Section: Discussionsupporting
confidence: 50%
“…In our study, we detected both viral RNA and viral antigen in different organs, especially in the three regions of the small intestine and the characteristic gut-associated lymphoid tissue (GALT)—the SR and appendix in the rabbit [24]. In our study, HEV RNA was detected in the liver, spleen, lung, lymph node, duodenum, and ileum of two inoculated rabbits at 14 dpi.…”
Section: Discussionmentioning
confidence: 57%
“…Positive signals were observed in the cytoplasm of hepatocytes and biliary epithelial cells, the epithelium of the bronchioles and alveoli, various cells in spleen and lymph node, the intestinal epithelium, and the follicle-associated epithelium (FAE) of the SR and appendix (Fig. 2) [24]. We detected no positive signals in any tissue in the negative group or in the kidneys of the inoculated group (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…In rabbits, apart from mesenteric lymph nodes and Peyer’s patches, the GALT which accounts for 50 % of the lymphoid tissue includes two specific structures: the sacculus rotundus, and the vermiform appendix. Both tissue types present M cells [ 36 ] which actively uptake and present particular antigens and microorganisms to the immune cells of the lymphoid follicle to induce an effective immune response [ 37 ]. Map has been reported to enter the domes of the Peyer’s patches through M cells [ 38 ] so orally ingested mycobacteria should end up in these sites and/or in caecal content and therefore we chose these specimens for our analysis.…”
Section: Discussionmentioning
confidence: 99%